A pilot study into the use of fossil fuels in golf course maintenance operations under Swedish conditions - Caple, Matthew (Cranfield University, 2008)
A method is proposed for measuring fuel consumption of golf course maintenance machinery within this study, in response to growing industry concerns to rising fuel prices and greenhouse gas emissions. The aim of this method is for its implementation as a maintenance optimisation tool to allow measurement, prediction and ultimate reduction in fuel consumption in maintenance. Volumetric fuel consumption was recorded for various operations by refilling fuel tanks back to the same levels prior to operations being performed. Results were presented initially in the primary unit of fuel consumption per cycle. A cycle was identified as the work required to perform an operation on a particular feature type, and which did not change in its nature between cycles. This in-situ method allowed fuel consumption measurements to be replicated for the same maintenance operations. Four secondary units to portray fuel consumption were created, one being area mown per litre of fuel, which allowed fuel consumption to be normalised by area and compared across golf courses. Key maintenance cycles were assessed on three different golf courses in Sweden. From the data collected, it was determined that rough mowing typically consumed the greatest amount of fuel per cycle and fairway mowing the greatest amount per year. Fairway mowing was also found to be the most fuel efficient operation. On the main test site, 86% of yearly diesel consumption was accounted for by operations that could be categorised into cycles. The proposed method was determined to be feasible for extended use due to its simplicity and ease of repetition. Normalisation of the data allows for further research to be undertaken into identifying inefficient operations and seeking methods to reduce fuel consumption. Further research should be undertaken over a whole golfing season to determine the accuracy for mean fuel consumption per cycle and to enable sporadic and smaller operations to be measured on an individual basis. The affect that distance travelled by machines between features has on cycle fuel consumption is the main recommendation for further adaptation of the method.
Keywords: fuel consumption; greenhouse gas emissions; Volumetric fuel consumption; rough mowing; maintenance operations